Toxicological Characterization and Phospholipase D Activity of the Venom of the Spider Sicarius thomisoides - Tomás Arán-Sekul; Ivanka Perčić-Sarmiento; Verónica Valencia; Nelly Olivero; José M. Rojas; Jorge E. Araya; Andrés Taucare-Ríos; Alejandro Catalán (Toxins, 2020)
Envenomation by Loxosceles spiders (Sicariidae family) has been thoroughly documented. However, little is known about the potential toxicity of members from the Sicarius genus. Only the venom of the Brazilian Sicarius ornatus spider has been toxicologically characterized. In Chile, the Sicarius thomisoides species is widely distributed in desert and semidesert environments, and it is not considered a dangerous spider for humans. This study aimed to characterize the potential toxicity of the Chilean S. thomisoides spider. To do so, specimens of S. thomisoides were captured in the Atacama Desert, the venom was extracted, and the protein concentration was determined. Additionally, the venoms were analyzed by electrophoresis and Western blotting using anti-recombinant L. laeta PLD1 serum. Phospholipase D enzymatic activity was assessed, and the hemolytic and cytotoxic effects were evaluated and compared with those of the L. laeta venom. The S. thomisoides venom was able to hydrolyze sphingomyelin as well as induce complement-dependent hemolysis and the loss of viability of skin fibroblasts with a dermonecrotic effect of the venom in rabbits. The venom of S. thomisoides showed intraspecific variations, with a similar protein pattern as that of L. laeta venom at 32–35 kDa, recognized by serum anti-LlPLD1. In this context, we can conclude that the venom of Sicarius thomisoides is similar to Loxosceles laeta in many aspects, and the dermonecrotic toxin present in their venom could cause severe harm to humans; thus, precautions are necessary to avoid exposure to their bite.